Comparison of the rain drop size distribution model in tropical region - Awang, M. A.; Din, Jafri (IEEE, 2004)
Information on raindrop size distribution (DSD) is important for prediction of the microwave signal attenuation due to rain, especially for high microwave frequency applications. The modeling of the raindrop size distribution in temperate and tropical regions is different because the tropical region experiences a heavy rain rate compared to the temperate region. This paper reports the comparison of the rain attenuation measurements from 38 GHz microwave links conducted at the Wireless Communication Center, Universiti Teknologi Malaysia (UTM) with the DSD model from Malaysia (KL-lognormal), Singapore, Brazil and Nigeria, using a lognormal distribution model. The lognormal parameters are determined by the predicted result from those countries. Thus, direct comparison of the rain attenuation measurement with the various DSD models could be made. The use of DSDs established for other climates and countries may result in prediction errors.